Study on causes of infertility among males attending infertility clinic at a rural teaching hospital in Andhra Pradesh - Dr. K. Pushpalatha; Dr R Sudhakar; Dr G Raja Pramila (Tropical Journal of Pathology and Microbiology)
Introduction: The incidence of infertility is increasing in developed and developing counties due to various causes, out of these many are preventable. The paper outlines study conducted to find the impact of various causes in male. Methods: All patients who attended the infertility clinics of GEMS Medical College, Srikakulam, between March 2014 to February 2015 were included in the study. Results: Infertility was high among men aged 20-25 and 30-40 years with 62.07% and 62.96%. Most common abnormality of infertility by microscopic study was found to be Pyospermia (38.46%), followed by Oligozoospermia (16.92%) and lowest abnormality is Hematospermia (3.08%). Conclusion: Infertility is high in 20-25 and 30-40 age group. Pyospermia was the most common microscopic abnormality; Preventable causes (87%) are commonest cause for infertility. Abnormality is found to be more than 50% among the patients.